Analisis Hukum terhadap Pseudo-Science dalam Bidang Pendidikan di Kalangan Masyarakat - Sylvia, Rena (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The development of the digital era has accelerated the spread of pseudo-science in the field of education, which has an impact on public understanding of valid science. Information that is not based on scientific evidence is easily spread through various digital platforms, causing confusion among the public and the world of education. This research aims to analyze aspects of legal protection against the spread of pseudo-science in education as well as the role of education in counteracting its negative impact. A normative juridical approach is used by reviewing relevant laws and regulations, such as Law No. 20/2003 on the National Education System, Law No. 11/2008 on Electronic Information and Transactions, and Law No. 8/1999 on Consumer Protection. The results show that although there are regulations that can be used to limit the negative spread of pseudo-science, there are still challenges in implementation and law enforcement in the digital era. In addition, education has a strategic role in improving scientific literacy and critical thinking to build public awareness of the importance of credible sources of information, as well as improving and developing curriculum based on humanity, cognitive intelligence, arts, and culture must also be developed so that scientific knowledge is not rigid, but also focuses on practical application in everyday life. Therefore, more specific policies are needed to regulate digital information as well as collaboration between the government, educational institutions, and the community to build a more effective system of legal protection and development of scientific insights against pseudo-science in education